Minari [videorecording (DVD)] - Chung, Lee Isaac, 1978-; Yeun, Steven; Han, Ye-ri, 1984-; Kim, Alan S. (Lionsgate, 2021)
A tender and sweeping story about what roots people that follows a Korean-American family that moves to a tiny Arkansas farm in search of their own American Dream. The family home changes completely with the arrival of their sly, foul-mouthed, but incredibly loving grandmother. Amidst the instability and challenges of this new life in the rugged Ozarks, this film shows the undeniable resilience of family and what really makes a home.